Religious Beliefs, Practices, and Representations as Humanly Enacted Realities: Lucian (circa 120-200) Addresses Sacrifices, Death, Divinity, and Fate - Prus, Robert (Qualitative Sociology Review, 2015)
Lucian of Samosata (circa 120-200) may be primarily envisioned as a poet-philosopher from the classical Roman era. However, the material he develops on religion not only anticipates important aspects of contemporary pragmatist/constructionist approaches to the sociology of religion but also provides some particularly compelling insights into religion as a humanly engaged realm of reality. Following an introduction to a pragmatist approach to the study of religion, this paper presents a synoptic overview of several of Lucian’s texts on religion. In addition to the significance of Lucian’s materials for comprehending an era of Roman and Greek civilization, as well as their more general sources of intellectual and aesthetic stimulation, these texts also provide an array of valuable transhistorical reference points and alert scholars in the field of religion to some ways in which the study of religion could be more authentically approached within the social sciences. The paper concludes with a consideration of the affinities of Lucian’s depictions of religion with pragmatist, interactionist, and associated approaches as this pertains to the study of religion as a realm of human involvement.